Risk assessment of Phlyctinus callosus for the EU - EFSA Panel on Plant Health (PLH); Claude Bragard; Paola Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Plant Health performed a quantitative risk assessment for the EU of Phlyctinus callosus (Coleoptera: Curculionidae), a polyphagous pest occurring in Australia, New Zealand and South Africa. The current risk assessment focused on potential pathways for entry, the climatic conditions allowing establishment, the expected spread capacity and the impact considering a time horizon of 10 years (2023–2032). The Panel identified the import of apples, cut flowers and table grapes as the most relevant entry pathways. Over the next 10 years, an annual median estimate of approximately 49.5 (90% certainty range, CR, ranging from 4.0 to 881.2) potential P. callosus founder populations are expected. When the probability of establishment is considered and climatic indicators are used to define the areas in the EU where establishment is possible, the model estimated a median of 1 founder population every 1.3 years (90% CR: 1 every 30.8 years to 23.3 per year) in the scenario where the areas are defined by the union of all the climatic indicators and 1 founder population every 11.9 years (90% CR: 1 every 256.6 years to 2.5 per year) in the scenario where establishment is possible only in the areas defined by the climatic indicator of minimum soil temperature. The estimated number of founder populations per year is mostly driven by the probability of establishment in the rural areas, infestation rate in table grapes and the probability of transfer to a suitable host in the rural area. The risk of entry for cut flowers and apples is substantially lower than the risk from the table grapes. If such founder populations were to establish, P. callosus is estimated to spread by natural dispersal and common agricultural practices at a rate of 15.5 m/year (90% CR 5.1–46.8 m/year) after a lag phase of 4.0 years (90% CR 1.3–8.7 years). The impact, expressed as percentage loss of the production directly attributable to P. callosus in the areas where establishment is possible and assuming farmers do not apply specific control measures was estimated at 0.5% (90% CR 0.01%–2.8%) for cut flowers/foliage, 5.2% (90% CR 2.2%–11.7%) for apples and 2% (90% CR 1.3%–5.2%) for table grapes. Options for risk reduction are discussed, but their effectiveness is not quantified.